Prospective evaluation of the motorized spiral enteroscope for previous incomplete colonoscopy - Al-Toma, Abdulbaqi; Oude Hergelink, Dorien M.; Tenthof van Noorden, Jacco; Koornstra, Jan Jacob (Endoscopy International Open, 2022)
Background and study aims A significant percentage of colonoscopies remain incomplete because of failure to intubate the cecum. The motorized spiral enteroscope (MSE) technique, originally developed for deep small bowel enteroscopy, may be an effective alternative technique in cases of incomplete examination of abnormally long colons (dolichocolon). We prospectively evaluated the success rate of cecal intubation, safety and the therapeutic consequences of using MSE after incomplete conventional colonoscopy.Patients and methods A total of 36 consecutive patients with an indication for diagnostic and/or therapeutic colonoscopy were prospectively enrolled in this multicenter trial. All patients had undergone at least one incomplete colonoscopy attributed to abnormally long colons. Patients with incomplete colonoscopy due to stenosis were excluded. Results Twenty-two men and 14 women (median age 66 years, range 35–82) were enrolled. Median procedure time was 30 minutes (range 16–50). Cecal intubation rate was 100 % and median cecal intubation time was 10 minutes (range 4–30). Abnormalities, mostly neoplastic lesions, were detected in 23 of 36 patients, corresponding to a diagnostic yield of 64 %. All these findings were in the right side of the colon and had not been described by the antecedent incomplete coloscopy. No adverse events occurred.Conclusions In case of a difficult and long colon, MSE is safe and effective for diagnostic and therapeutic colonoscopy. It may provide an attractive solution to accomplish completeness of previous incomplete colonoscopies in these patients.